2017
DOI: 10.1103/physrevlett.118.236402
|View full text |Cite
|
Sign up to set email alerts
|

Topological Insulators in Amorphous Systems

Abstract: Our understanding of topological insulators is based on an underlying crystalline lattice where the local electronic degrees of freedom at different sites hybridize with each other in ways that produce nontrivial band topology, and the search for material systems to realize such phases have been strongly influenced by this. Here we theoretically demonstrate topological insulators in systems with a random distribution of sites in space, i. e., a random lattice. This is achieved by constructing hopping models on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
136
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(144 citation statements)
references
References 62 publications
8
136
0
Order By: Relevance
“…Previously it has been shown that various hopping models with randomly distributed dopants will undergo a topological phase transition at sufficiently high density [2,11]. The purpose of this work is to establish a quantitative description of this phase transition in representative topological models with randomly-generated geometries in two dimensions.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Previously it has been shown that various hopping models with randomly distributed dopants will undergo a topological phase transition at sufficiently high density [2,11]. The purpose of this work is to establish a quantitative description of this phase transition in representative topological models with randomly-generated geometries in two dimensions.…”
mentioning
confidence: 97%
“…The Z 2 invariant can be evaluated through a configuration-averaged spin Bott indexC s [23], for which we assume a similar scaling form. It should be stressed that while the scaling hypotheses for topological invariants are superficially similar to the scaling of percolation probability [17], they characterize the topology of quantum ground states of models (1), (2), which is conceptually completely independent on the classical percolation problem.…”
mentioning
confidence: 99%
“…9,10 A particularly interesting and recent setting to explore such physics occur in the three dimensional Z 2 free fermion SPTs (e.g., the topological band insulators (TBI)), protected by timereversal symmetry (TRS) and particle number conservation, in simple hopping models on a structurally amorphous network. 9 The role of potential disorder in three dimensional Z 2 TBI and associated disorder driven quantum have transitions have so far almost exclusively investigated using a variety of methods [11][12][13][14][15][16][17][18] starting with an underlying crystal. Interestingly in this context Ref.…”
mentioning
confidence: 99%
“…Model for amorphous Z 2 insulator in three spatial dimensions : Our starting point is the the hopping Hamiltonian introduced in Ref. 9 :…”
mentioning
confidence: 99%
“…This approach, while efficacious, fails when no such structure exists i.e., for aperiodic systems, including amorphous, quasiperiodic, and fractal systems. Nonetheless, topological phenomena have been shown to exist in both amorphous [39][40][41][42][43][44] and quasiperiodic [45][46][47][48][49][50] systems.…”
mentioning
confidence: 99%